The Structural Sources of Socioeconomic Inequalities in Health: A Cross-National Perspective - Lucy Barnes; Peter A. Hall; Rosemary C. R. Taylor (Socius, 2023)
This article investigates how macro-level structures condition the sources of socioeconomic inequalities in health. Drawing on multiple social science disciplines, the authors develop theoretically grounded propositions about how different types of welfare states, varieties of capitalism, and social structures give rise to cross-national variations in the sources of health inequalities. They consider how these macro-level structures affect the distribution of five key resources important to health, estimate the relative contribution that each resource makes to health inequalities, and compare those contributions in 21 developed democracies. Moving beyond a current literature focused on welfare states, the authors show how different types of political economies and social structures also condition the health gradient. This research carries implications for policy and suggests agendas for further investigation into the relationship between macro-level structures and inequalities in health.